1993
DOI: 10.1128/jb.175.4.1173-1175.1993
|View full text |Cite
|
Sign up to set email alerts
|

A dominant sulfhydryl-containing protein in the outer membrane of Neisseria gonorrhoeae

Abstract: By using a method that labels sulfhydryl-containing proteins in situ, we (6,14,15). It reacts selectively with the thiol anion of sulfhydryls, crosses biological membranes, and does not significantly alter the molecular weight of proteins (6,14,15).We have used mB to label the sulfhydryl-containing proteins of the outer membrane of Neissena gonorrhoeae. By labeling during growth, we have eliminated the effect of oxidative changes that occur during harvesting and preparation of fractions, thereby detecting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…32−34 In the present study, we found that increasing the concentration of glucose, a common carbon source that can be utilized by a wide range of bacteria, in the M9 minimal medium significantly increases the concentration of sulfhydryl sites within the cell envelopes of the three bacterial species studied (Figure 2b), suggesting that carbon utilization is required for the synthesis of bacterial sulfhydryl sites. Although sulfhydryl sites themselves do not contain carbon, some previous studies suggest that sulfhydryl sites are predominantly present attached to proteins within cell envelopes, 14,35,36 and carbon is an essential element in the framework of proteins. It is likely that the cells require a certain concentration of carbon source in order to have enough bioavailable carbon to construct sulfhydryl-containing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…32−34 In the present study, we found that increasing the concentration of glucose, a common carbon source that can be utilized by a wide range of bacteria, in the M9 minimal medium significantly increases the concentration of sulfhydryl sites within the cell envelopes of the three bacterial species studied (Figure 2b), suggesting that carbon utilization is required for the synthesis of bacterial sulfhydryl sites. Although sulfhydryl sites themselves do not contain carbon, some previous studies suggest that sulfhydryl sites are predominantly present attached to proteins within cell envelopes, 14,35,36 and carbon is an essential element in the framework of proteins. It is likely that the cells require a certain concentration of carbon source in order to have enough bioavailable carbon to construct sulfhydryl-containing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not clear why the P. putida cells contain 466 such high concentrations of cell surface sulfhydryl sites when they are cultured in the LB10 467 medium, Choi et al (2014) found that P. putida cells cultured in the LB10 medium have more than a three-fold higher protein content within their EPS matrix compared to P. putida cells grown in 469 two other minimal media. Proteins are likely the primary hosts of sulfhydryl sites both within cell envelopes and on EPS material (Norrod et al, 1993;Fein et al, 2019). Therefore, our findings suggest that the energy source and perhaps other environmental factors during cell growth play important roles in the production of surface proteins and hence cell surface sulfhydryl binding sites by P. putida (Choi et al, 2014).…”
Section: Discussion 456mentioning
confidence: 78%